Soaring prices of food staples and the implications for food security: The case of rice in Edo state, Nigeria - Egware, R A; Orewa, S I (Revista Bio Ciencias, 2016)
This paper examined the soaring prices of food staples with emphasis on rice in Edo State, Nigeria covering the period 1990-2005. Specifically, the study examined the nature of the price movement and the quarterly trend between markets for rice in Edo State, Nigeria and the price relationship of rice within the markets. The rates of increase in price of rice in the rural and urban markets were also determined. Also, the differences in rice prices between the rural and urban markets were tested if they were significant. The prices used were derived from the daily prices of rice collected by staff of the Edo State Agricultural Development Programme (EADP) from the various markets in Edo State, Nigeria. The data were analyzed using simple descriptive statistics (such as means, standard deviations, tables, graphs etc) and multiple regression analysis. The study revealed that the price of rice for both markets (rural and urban) started rising from the second quarter through to the third before peaking in the fourth quarter. Generally, urban market prices were higher than that of the rural market prices. However, for four consecutive years (1996 – 1999), the rural market prices were higher than urban prices by 7.14%, 3.46%, 1.12% and 4.89% respectively. The observed mean annual price increase was 15.56% and 16.49% for rural and urban markets respectively. When the differences between the rural and urban market prices for the period were compared using the Student t-test, they were significantly different from each other at the 95% confidence level. The regression analysis showed that the price of rice had no significant relationship with the prices of other food staples in the rural market. However, the relationships observed were both complementary and competitive. The urban markets had no competitive relationship. Due to the disparity in prices between the rural and urban markets, it is recommended that government should direct her effects towards stabilizing the price of fuel and create motorable roads in the rural areas where rice is produced in order to close up the considerable price disparity between the rural and urban markets.